Влипсики: [повесть-сказка] / Катя Матюшкина ; [стихи Александра Тимофеева] - Матюшкина Екатерина Александровна (Внеклассное чтение, 2010)
Экземпляры: ф.5,ДБ (20111102) / Инвентарный номер: 43470 / Цена: 173.52 / Авт.знак: М 35 / ББК: 84(2Рос=Рус)6